Lithium-sulfur battery difunctional diaphragm and preparation method thereof

By using nickel-cobalt diatom catalyst base material as separator loading material in lithium-sulfur batteries, the problem of poor circulation performance of lithium-sulfur batteries is solved, and more efficient sulfur redox kinetics and shuttle effect inhibition is achieved, which improves the battery's Overall performance and security.

CN119481568APending Publication Date: 2025-02-18SOUTHWEAT UNIV OF SCI & TECH +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411696257.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Lithium sulfur batteries have failed to commercialize due to the slow sulfide redox kinetics and shuttle effect.

Method used

A carbon-based material of nickel-cobalt diatom catalyst is used as the loading material for the separator, and an electrocatalyst material with a porous and large specific surface area is prepared by high-temperature pyrolysis, which promotes sulfur redox kinetics and inhibits the shuttle effect.

Benefits of technology

It significantly improves the circulation performance of lithium sulfur batteries, reduces the generation of lithium dendrites, protects the separator, and ensures the safety and efficiency of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481568A_ABST
    Figure CN119481568A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of new energy materials and devices, and discloses a lithium-sulfur battery difunctional diaphragm and a preparation method thereof, the lithium-sulfur battery difunctional diaphragm comprises a diaphragm substrate and a load slurry, the load slurry is coated on the surface of the diaphragm substrate; the loaded slurry comprises an electrocatalyst material, and the electrocatalyst material is a monatomic catalyst carbon-based material / diatomic catalyst carbon-based material. The monatomic catalyst carbon-based material is a nickel monatomic catalyst carbon-based material or a cobalt monatomic catalyst carbon-based material; the diatomic catalyst carbon-based material is a nickel-cobalt diatomic catalyst carbon-based material. The nickel-cobalt diatomic catalyst coupled carbon-based material is applied to the field of lithium-sulfur batteries and serves as a lithium-sulfur battery diaphragm modification material, sulfur redox kinetics can be promoted, the shuttle effect can be inhibited, lithium ion flux can be induced, so that lithium dendrite growth is inhibited, and finally the cycle performance of the lithium-sulfur batteries is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new energy materials and devices, and in particular to a lithium-sulfur battery dual-function diaphragm and a preparation method thereof. Background Art

[0002] The statements in this section merely provide background information related to the present disclosure and may not constitute prior art.

[0003] Among many energy storage technologies, lithium-ion batteries have attracted much attention due to their high mass specific energy and volume energy density. However, the theoretical specific capacity and actual energy density of lithium-ion batteries based on the "deintercalation" theory are far from meeting people's requirements. Breaking through their capacity limit is a major technical challenge currently faced.

[0004] Lithium-sulfur batteries have a high theoretical specific capacity (1675 mAh g -1 ) and energy density (2600Wh kg -1 ), is considered to be a promising candidate for high energy density energy storage system, but the commercialization process of lithium sulfur batteries is limited by the following problems; (1) The positive electrode active material sulfur and the final discharge product lithium sulfide are electronic / ion insulating materials, which not only leads to low utilization of active materials, but also makes lithium sulfide deposited on the electrode and difficult to activate, causing battery capacity decay. (2) The shuttle effect caused by the diffusion and migration of soluble lithium polysulfide in the electrolyte during charging and discharging will lead to serious loss of active materials and reduced battery coulombic efficiency; (3) The volume change of electrode materials during charging and discharging is large, which will cause damage to the electrode structure; (4) Lithium metal reacts with most electrolytes and forms an unstable SEI film on the surface. During its charging and discharging process, lithium dendrites will be generated, which will pierce the diaphragm and cause battery short circuit. Among them, the slow sulfur redox kinetics and the shuttle effect are the main reasons why lithium sulfur batteries have not been commercialized.

[0005] In view of this, this application is hereby filed. Summary of the invention

[0006] The technical problem to be solved by the present invention is that the lithium-sulfur battery prepared by the prior art has poor cycle performance due to slow sulfur redox kinetics and the shuttle effect. The purpose is to provide a lithium-sulfur battery bifunctional diaphragm and a preparation method thereof to promote sulfur redox kinetics, thereby inhibiting the shuttle effect and reducing the formation of lithium dendrites, and ultimately improving the cycle performance of the lithium-sulfur battery.

[0007] The technical solution of the present invention is as follows:

[0008] A lithium-sulfur battery dual-function diaphragm comprises a diaphragm substrate and a loading slurry, wherein the loading slurry is coated on the surface of the diaphragm substrate; the loading slurry comprises an electrocatalyst material, and the electrocatalyst material is a single-atom catalyst carbon-based material / a double-atom catalyst carbon-based material.

[0009] In traditional lithium-sulfur batteries, severe shuttle effects cause loss of active materials and reduced coulombic efficiency. At the same time, dissolved polysulfides diffuse to the negative electrode and react with lithium, and the generated Li2S is deposited on the surface of the negative electrode, resulting in negative electrode passivation, which in turn affects the battery's cycle performance. The present invention provides a lithium-sulfur battery bifunctional diaphragm, which uses bimetallic ZIFs as precursors, and obtains a porous, large specific surface area polar electrocatalyst material after high-temperature pyrolysis, which can not only promote sulfur redox kinetics and inhibit the shuttle effect, but also induce lithium ion flux to inhibit lithium dendrite growth, ultimately improving the cycle performance of lithium-sulfur batteries.

[0010] Preferably, the diaphragm substrate is a PP diaphragm.

[0011] Preferably, the loading slurry further comprises a binder and a conductive carbon material.

[0012] Preferably, the binder comprises PVDF.

[0013] Preferably, the conductive carbon material comprises conductive carbon black.

[0014] Preferably, the single-atom catalyst carbon-based material is a nickel single-atom catalyst carbon-based material or a cobalt single-atom catalyst carbon-based material;

[0015] The diatomic catalyst carbon-based material is a nickel-cobalt diatomic catalyst carbon-based material.

[0016] According to a preferred embodiment, the nickel-cobalt diatomic catalyst carbon-based material is prepared by the following method:

[0017] Step S1: first synthesizing bimetallic Zn / Co-ZIFs by a common solvent method;

[0018] Step S2: Ni 2+ adsorbed on bimetallic Zn / Co-ZIFs to form Zn / Co / Ni-ZIFs precursor;

[0019] Step S3: finally, pyrolyzing and carbonizing the Zn / Co / Ni-ZIFs precursor at high temperature;

[0020] Step S4: acid-wash the product of step S3 to obtain a nickel-cobalt diatomic catalyst carbon-based material.

[0021] According to a preferred embodiment, the nickel-cobalt diatomic catalyst carbon-based material is specifically prepared by the following method:

[0022] Step S1: Mixing a methanol solution of zinc nitrate and cobalt nitrate with a methanol solution of methylimidazole, stirring, centrifuging, and drying to obtain a product Zn / Co-ZIFs;

[0023] Step S2: ultrasonically disperse the product obtained in step S1 in cyclohexane, dropwise add nickel nitrate aqueous solution, stir, centrifuge, and dry to obtain precursor Zn / Co / Ni-ZIFs;

[0024] Step S3: transferring the precursor Zn / Co / Ni-ZIFs obtained in step S2 into a tube furnace and pyrolyzing it under Ar atmosphere;

[0025] Step S4: soak the pyrolysis product prepared in step S3 in a sulfuric acid solution, wash it by centrifugation with deionized water until the pH reaches neutral, and vacuum dry it to obtain a lithium-sulfur battery diaphragm modification material coupled with a nickel-cobalt diatomic catalyst carbon-based material.

[0026] According to a preferred embodiment, in step S3, the temperature is 5.0°C min-1 under an Ar atmosphere. -1 The pyrolysis was carried out at a heating rate of 900°C to 940°C, and the temperatures at 400°C and 800°C were maintained for 1 h respectively, and the final temperature was maintained for 5 h.

[0027] According to a preferred embodiment, the final temperature is 910°C-940°C.

[0028] According to a preferred embodiment, the final temperature is 920°C.

[0029] According to a preferred embodiment, the thickness of the load slurry coated on the surface of the diaphragm substrate is 100 μm.

[0030] Another aspect of the present invention provides a nickel-cobalt diatomic catalyst carbon-based material, which is prepared by the following method:

[0031] Step S1: Mixing a methanol solution of zinc nitrate and cobalt nitrate with a methanol solution of methylimidazole, stirring, centrifuging, and drying to obtain a product Zn / Co-ZIFs;

[0032] Step S2: ultrasonically disperse the product obtained in step S1 in cyclohexane, dropwise add nickel nitrate aqueous solution, stir, centrifuge, and dry to obtain precursor Zn / Co / Ni-ZIFs;

[0033] Step S3: transferring the precursor Zn / Co / Ni-ZIFs obtained in step S2 into a tube furnace and pyrolyzing it under Ar atmosphere;

[0034] Step S4: Soak the pyrolysis product prepared in step S3 in a sulfuric acid solution, centrifuge and wash with deionized water until the pH is neutral, and vacuum dry to obtain a lithium-sulfur battery diaphragm modification material coupled with a nickel-cobalt diatomic catalyst carbon-based material. Preferably, the single-atom catalyst carbon-based material is, for example, a nickel single-atom catalyst carbon-based material or a cobalt single-atom catalyst carbon-based material. The diatomic catalyst carbon-based material is, for example, a nickel-cobalt diatomic catalyst carbon-based material.

[0035] Another aspect of the present invention provides a nickel single atom catalyst carbon-based material, which is prepared by the following method:

[0036] Step S1: ultrasonically dispersing ZIF-8 powder in n-hexane, adding nickel nitrate aqueous solution, stirring, centrifuging, and drying to obtain Zn / Ni-ZIFs precursor;

[0037] Step S2: transferring the Zn / Ni-ZIFs precursor to a tube furnace for pyrolysis and keeping the temperature;

[0038] Step S3: The pyrolysis product is acid-washed, centrifuged, and dried to obtain a lithium-sulfur battery diaphragm modification material - a nickel single-atom catalyst carbon-based material.

[0039] Another aspect of the present invention provides a cobalt single atom catalyst carbon-based material, which is prepared by the following method:

[0040] S1: Disperse ZIF-8 powder in n-hexane by ultrasonication at room temperature, then add nickel nitrate aqueous solution dropwise and stir vigorously. Centrifuge the precipitate and vacuum dry to obtain Zn / Ni-ZIFs precursor;

[0041] S2: The precursor Zn / Ni-ZIFs obtained in step S1 is transferred to a tube furnace and pyrolyzed at a heating rate under an Ar atmosphere;

[0042] S3: soaking the pyrolysis product obtained in step S2 in a sulfuric acid solution, washing it by centrifugation with deionized water until the pH reaches neutral, and vacuum drying it to obtain a nickel single-atom catalyst carbon-based material for a lithium-sulfur battery diaphragm modification material.

[0043] On the other hand, the present invention provides the use of the aforementioned nickel-cobalt diatomic catalyst carbon-based material, cobalt single atom catalyst carbon-based material and nickel single atom catalyst carbon-based material in lithium-sulfur batteries to promote sulfur redox kinetics to inhibit the shuttle effect.

[0044] The present invention also provides a method for preparing a lithium-sulfur battery dual-function diaphragm, the method steps comprising:

[0045] Step S1: uniformly mixing the electrocatalyst material with the conductive carbon material, the binder and NMP until the slurry is in a flowing honey-like state, thereby obtaining a diaphragm-loaded slurry;

[0046] Step S2: Use a 100 μm scraper to coat the slurry on the surface of the diaphragm substrate, dry the coated diaphragm naturally in the air, and then place it in a vacuum oven for drying to obtain a lithium-sulfur battery dual-function diaphragm.

[0047] Preferably, the following three electrocatalyst materials are used respectively: nickel-cobalt diatomic catalyst carbon-based material, nickel single-atom catalyst carbon-based material, and cobalt single-atom catalyst carbon-based material modification, and the bifunctional diaphragms modified with nickel-cobalt diatomic catalyst carbon-based material, nickel single-atom catalyst carbon-based material, and cobalt single-atom catalyst carbon-based material are prepared according to the above method respectively.

[0048] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0049] 1. On the one hand, the present invention provides a lithium-sulfur battery bifunctional diaphragm, which is modified by a nickel-cobalt diatomic catalyst carbon-based material, a nickel single-atom catalyst carbon-based material or a cobalt single-atom catalyst carbon-based material, and provides an application of a single-atom catalyst carbon-based material / a diatomic catalyst carbon-based material in a lithium-sulfur battery bifunctional diaphragm. Compared with the prior art, the modified diaphragm can promote sulfur redox kinetics, thereby inhibiting the shuttle effect and reducing the formation of lithium dendrites, and ultimately improving the cycle performance of the lithium-sulfur battery.

[0050] 2. On the other hand, the present invention provides a new preparation method for single-atom catalyst carbon-based materials / double-atom catalyst carbon-based materials. The preparation method is different from conventional high-temperature pyrolysis and impregnation methods, and has the following advantages: bimetallic ZIFs are used as precursors, and then single-atom / double-atom catalyst carbon-based materials are obtained by high-temperature pyrolysis. The ZIFs-derived carbon materials not only have high porosity, abundant active sites, and diverse and adjustable components, but also have a simple preparation process, and the double-atom catalyst carbon-based materials with dual functional coupling can be obtained through adjustable precursors.

[0051] 3. Another aspect of the present invention provides a method for preparing a dual-function diaphragm for a lithium-sulfur battery. The aforementioned electrocatalyst material is mixed with other auxiliary materials and then coated on the surface of the diaphragm. After natural drying, the dual-function diaphragm for a lithium-sulfur battery can be obtained by drying. The diaphragm simultaneously performs isolation and catalytic functions, which is beneficial to promoting sulfur redox kinetics, thereby inhibiting the polysulfide shuttle effect, improving the utilization rate of active sulfur, and promoting lithium ion flux, thereby inhibiting the growth of lithium dendrites, protecting the safety of the diaphragm, and preventing the diaphragm from being punctured, thereby ensuring the safety of the lithium-sulfur battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 This is a SEM image of the coupled nickel-cobalt diatomic catalyst carbon-based material described in Example 1;

[0053] Figure 2This is a SEM image of the nickel single atom catalyst carbon-based material described in Example 2;

[0054] Figure 3 This is a SEM image of the cobalt single atom catalyst carbon-based material described in Example 3;

[0055] Figure 4 XRD diagrams of the three catalyst carbon-based materials described in Examples 1-3;

[0056] Figure 5 This is the HAADF-STEM image of the coupled nickel-cobalt diatomic catalyst carbon-based material described in Example 1;

[0057] Figure 6 The cycle performance diagram of the diaphragm prepared in Examples 1-3 and Comparative Example 1 at a current density of 0.5C ( Figure 6 It is a double Y-axis cycle performance diagram, the left axis is the discharge specific capacity, and the right axis is the charge and discharge efficiency);

[0058] Figure 7 The diagram is a rate performance diagram of the diaphragms prepared in Examples 1-3 and Comparative Example 1 at different current densities. DETAILED DESCRIPTION

[0059] The specific embodiments listed in the present invention are only examples of the present invention, and the present invention is not limited to the specific embodiments described below. For those skilled in the art, any equivalent modifications and substitutions to the embodiments described below are also within the scope of the present invention. Therefore, the equal transformations and modifications made without departing from the spirit and scope of the present invention should be included in the scope of the present invention. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturers are not specified for all reagents or instruments, they are all conventional products that can be purchased commercially. In order to better illustrate the present invention, numerous specific details are given in the specific embodiments below. It should be understood by those skilled in the art that the present invention can also be implemented without certain specific details. In other embodiments, the methods, means, equipment and steps well known to those skilled in the art are not described in detail in order to highlight the purport of the present invention.

[0060] Unless otherwise defined, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art. Unless otherwise specified, the units used in this specification are all international standard units, and the numerical values ​​and numerical ranges appearing in the present invention should be understood to include the inevitable systematic errors in industrial production.

[0061] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0062] Example 1

[0063] In traditional lithium-sulfur batteries, the slow sulfur redox kinetics and shuttle effect cause the poor cycling performance of lithium-sulfur batteries.

[0064] The coupled nickel-cobalt diatomic catalyst carbon-based material was prepared by the following steps:

[0065] S1: Mix 5.0g of zinc nitrate and 1.6g of cobalt nitrate in methanol with 3.7g of 2-methylimidazole in methanol and stir at room temperature for 24h. After standing, centrifuge and wash the precipitate with methanol three times to remove the unreacted reagents. Finally, vacuum dry at 60℃ for 12h to obtain Zn / Co-ZIFs.

[0066] S2: 1 g Zn / Co-ZIFs powder was ultrasonically dispersed in 100.0 mL n-hexane for 30 min, and then 0.5 mL nickel nitrate aqueous solution (100 mg mL -1 ). The mixed solution was vigorously stirred for 3 h, and finally the precipitate was centrifuged and vacuum dried at 60 °C for 12 h to obtain the Zn / Co / Ni-ZIFs precursor;

[0067] S3: 2.0 g Zn / Co / Ni-ZIFs precursor was transferred into a tube furnace and heated at 5.0 °C min-1 under Ar atmosphere. -1 The final temperature was 920℃. The samples were kept at 400℃ and 800℃ for 1h each and at the final temperature for 5h.

[0068] S4: Soak the pyrolysis product in a 0.5M sulfuric acid solution. Wash the black solid precipitate with deionized water by centrifugation until the pH is neutral, and vacuum dry it at 60°C for 12 hours to obtain a nickel-cobalt diatomic catalyst carbon-based material.

[0069] The preparation of a lithium-sulfur battery bifunctional diaphragm comprises the following steps:

[0070] S1: Disperse the conductive carbon material Super P, the binder PVDF (polyvinylidene fluoride) and the nickel-cobalt diatomic catalyst carbon-based material in NMP (N-methylpyrrolidone) to obtain a diaphragm-loaded slurry. The mass ratio of the conductive carbon material Super P to the nickel-cobalt diatomic catalyst carbon-based material is 1:1, the mass ratio of PVDF to the nickel-cobalt diatomic catalyst carbon-based material is 9:2, and the nickel-cobalt diatomic catalyst carbon-based material is the coupled nickel-cobalt diatomic catalyst carbon-based material prepared by the aforementioned method of this embodiment;

[0071] S2: The above-mentioned membrane-loaded slurry is coated on one side of the PP membrane with a thickness of 100 μm, and the coated membrane is dried in a vacuum oven at 60°C for 12 hours to obtain a lithium-sulfur battery bifunctional membrane modified by a coupled nickel-cobalt diatomic catalyst carbon-based material.

[0072] The button cell is assembled using the lithium-sulfur battery bifunctional diaphragm modified by the coupled nickel-cobalt diatomic catalyst carbon-based material prepared above, and the specific steps are as follows:

[0073] S1: The obtained diaphragm is cut into discs with a diameter of 19 mm with a cutter for lithium-sulfur battery assembly, and button batteries are assembled with the diaphragm prepared in Example 1 in a glove box with an argon atmosphere; the diaphragm is a PP diaphragm, and the electrolyte used for battery assembly is a lithium-sulfur electrolyte prepared by dissolving 1M lithium bistrifluoromethylsulfonimide (LiTFSI) containing 2wt.% LiNO3 in ethylene glycol dimethyl ether and 1,3-dioxolane in a volume ratio of 1:1.

[0074] S2: Place the assembled button cell in a 28°C constant temperature box and use a battery testing system to perform an electrochemical performance test on the assembled cell.

[0075] Example 2

[0076] The nickel single atom catalyst carbon-based material was prepared by the following steps:

[0077] S1: 1.0 g ZIF-8 powder was ultrasonically dispersed in 100.0 mL n-hexane at room temperature for 30 min, and 0.5 mL nickel nitrate aqueous solution (100 mg mL -1 ) was stirred vigorously for 3 h, and vacuum dried at 60 °C for 12 h to obtain a Zn / Ni-ZIFs precursor;

[0078] S2: 2.0 g Zn / Ni-ZIFs precursor was transferred into a tube furnace and heated at 5.0 °C min-1 under Ar atmosphere. -1 The final temperature was 920℃. The samples were kept at 400℃ and 800℃ for 1h each and at the final temperature for 5h.

[0079] S3: The pyrolysis product was immersed in a 0.5 M sulfuric acid solution. The black solid precipitate was washed by centrifugation with deionized water until the pH value was neutral, and vacuum dried at 60° C. for 12 h to obtain a nickel single atom catalyst carbon-based material.

[0080] The preparation of a lithium-sulfur battery bifunctional diaphragm comprises the following steps:

[0081] S1: Disperse Super P, PVDF and nickel single atom catalyst carbon-based material in NMP to obtain a diaphragm-loaded slurry. The mass ratio of Super P to nickel single atom catalyst carbon-based material is 1:1, the mass ratio of PVDF to nickel single atom catalyst carbon-based material is 9:2, and the lithium-sulfur battery bifunctional diaphragm modified by nickel single atom catalyst carbon-based material; the nickel single atom catalyst carbon-based material is the nickel single atom catalyst carbon-based material prepared by the aforementioned method of this embodiment;

[0082] S2: The above-mentioned membrane-loaded slurry is coated on one side of the PP membrane with a thickness of 100 μm, and the coated membrane is dried in a vacuum oven at 60° C. for 12 h to obtain a lithium-sulfur battery bifunctional membrane modified with a nickel single-atom catalyst carbon-based material.

[0083] The button cell is assembled with the lithium-sulfur battery bifunctional diaphragm modified with the nickel single atom catalyst carbon-based material prepared in the present embodiment, and the specific steps are as follows:

[0084] S1: The obtained diaphragm is cut into discs with a diameter of 19 mm with a cutter for lithium-sulfur battery assembly, and button batteries are assembled with the diaphragm prepared in Example 2 in a glove box with an argon atmosphere; the diaphragm is a PP diaphragm, and the electrolyte used for battery assembly is a lithium-sulfur electrolyte prepared by dissolving 1M lithium bistrifluoromethylsulfonimide (LiTFSI) containing 2wt.% LiNO3 in ethylene glycol dimethyl ether and 1,3-dioxolane in a volume ratio of 1:1.

[0085] S2: Place the assembled button cell in a 28°C constant temperature box and use a battery testing system to perform an electrochemical performance test on the assembled cell.

[0086] Example 3

[0087] The cobalt single atom catalyst carbon-based material is prepared according to the following steps:

[0088] S1: Mix 5.0g of zinc nitrate and 1.6g of cobalt nitrate in methanol with 3.7g of 2-methylimidazole in methanol and stir at room temperature for 24h. After standing, centrifuge and wash the precipitate with methanol three times to remove the unreacted reagents. Finally, vacuum dry at 60℃ for 12h to obtain Zn / Co-ZIFs.

[0089] S2: 2.0 g Zn / Co-ZIFs precursor was transferred into a tube furnace and heated at 5.0 °C min-1 under Ar atmosphere. -1 The final temperature was 920℃. The samples were kept at 400℃ and 800℃ for 1h each and at the final temperature for 5h.

[0090] S3: Soak the pyrolysis product in a 0.5M sulfuric acid solution. Wash the black solid precipitate with deionized water by centrifugation until the pH is neutral, and vacuum dry it at 60°C for 12 hours to obtain a cobalt single atom catalyst carbon-based material.

[0091] The preparation of a lithium-sulfur battery separator comprises the following steps:

[0092] S1: Disperse Super P, PVDF and cobalt single atom catalyst carbon-based material in NMP to obtain a diaphragm-loaded slurry. The mass ratio of Super P to cobalt single atom catalyst carbon-based material is 1:1, the mass ratio of PVDF to cobalt single atom catalyst carbon-based material is 9:2, and the cobalt single atom catalyst carbon-based material is the cobalt single atom catalyst carbon-based material prepared in this embodiment;

[0093] S2: The mixed slurry is coated on one side of the PP diaphragm with a thickness of 100 μm, and the coated diaphragm is dried in a vacuum oven at 60° C. for 12 h to obtain a lithium-sulfur battery bifunctional diaphragm modified with a cobalt single-atom catalyst carbon-based material.

[0094] The button cell is assembled with the lithium-sulfur battery bifunctional diaphragm modified with the cobalt single atom catalyst carbon-based material prepared in the present embodiment, and the specific steps are as follows:

[0095] S1: The obtained diaphragm is cut into discs with a diameter of 19 mm with a cutter for lithium-sulfur battery assembly, and button batteries are assembled with the diaphragm prepared in Example 3 in a glove box with an argon atmosphere; the diaphragm is a PP diaphragm, and the electrolyte used for battery assembly is a lithium-sulfur electrolyte prepared by dissolving 1M lithium bistrifluoromethylsulfonimide (LiTFSI) containing 2wt.% LiNO3 in ethylene glycol dimethyl ether and 1,3-dioxolane in a volume ratio of 1:1.

[0096] S2: Place the assembled button cell in a 28°C constant temperature box and use a battery testing system to perform an electrochemical performance test on the assembled cell.

[0097] Comparative Example 1

[0098] Assembly of lithium-sulfur button cells with common separators:

[0099] In a glove box filled with argon, the positive electrode, diaphragm, lithium sheet, gasket, and spring are assembled in the order of the positive electrode, diaphragm, lithium sheet, gasket, and spring. The battery accessories are 2032 button batteries, the diaphragm is a PP diaphragm, and the electrolyte used for battery assembly is a lithium sulfur electrolyte prepared by dissolving 1M lithium bistrifluoromethanesulfonimide (LiTFSI) containing 2wt.% LiNO3 in ethylene glycol dimethyl ether and 1,3-dioxolane in a volume ratio of 1:1.

[0100] Performance test of the coupled nickel-cobalt diatomic catalyst carbon-based material prepared in Examples 1-6 of the present application:

[0101] (I) SEM and XRD characterization of lithium-sulfur battery separator modified materials:

[0102] (1) SEM and XRD analysis were performed on the nickel-cobalt diatomic catalyst carbon-based material, nickel single-atom catalyst carbon-based material and cobalt single-atom catalyst carbon-based material prepared in Examples 1-3 of the present invention. The results are as follows: Figure 1 , Figure 2 , Figure 3 , Figure 4 shown.

[0103] like Figure 1-3 It can be seen that the nickel-cobalt diatomic catalyst carbon-based material, the nickel single-atom catalyst carbon-based material and the cobalt single-atom catalyst carbon-based material prepared in Examples 1-3 have a rhombic dodecahedron structure.

[0104] like Figure 4 It can be seen that only amorphous graphite carbon diffraction peaks were observed at 26° and 44°, and no characteristic diffraction peaks related to nickel and cobalt were found. The test results showed that there were no metal / metal compound nanoparticles present.

[0105] (2) HAADF-STEM characterization of carbon-based materials coupled with nickel-cobalt diatomic catalysts.

[0106] In order to observe the distribution of nickel and cobalt atoms more intuitively at the atomic level, the inventors conducted HAADF-STEM analysis on the coupled nickel-cobalt diatomic catalyst carbon-based material prepared in Example 1 of the present invention. The results are as follows: Figure 5 shown.

[0107] Since Ni and Co elements have greater atomic number contrast than N and C, the brighter parts in the image represent Ni and Co atoms. Figure 3 It can be seen that no isolated dispersed Ni or Co atoms were observed in the coupled Ni-Co diatomic catalyst carbon-based material, and Figure 5 It can be seen that a large part of the bright spots come from atomic pairs distributed in the carbon matrix, which intuitively illustrates that the Ni and Co atoms in the material exist in the form of atomic pairs, and no metal nanoparticles or clusters are observed.

[0108] (II) Performance test of lithium-sulfur battery of the present invention:

[0109] (1) Cyclic performance test

[0110] The lithium-sulfur batteries assembled in Examples 1-3 and Comparative Example 1 were subjected to a 100-cycle cycle performance test at 0.5C on a Xinwei test instrument. The results are as follows: Figure 6 As shown. ( Figure 6 It is a double Y-axis cycle performance diagram, the left axis is the discharge specific capacity, and the right axis is the charge and discharge efficiency).

[0111] Since the lithium-sulfur battery separator is modified by coupling nickel-cobalt diatomic catalyst carbon-based materials, nickel single-atom catalyst carbon-based materials and cobalt diatomic catalyst carbon-based materials, the coupling nickel-cobalt diatomic catalyst carbon-based materials, nickel single-atom catalyst carbon-based materials and cobalt diatomic catalyst carbon-based materials can promote sulfur redox kinetics, inhibit the shuttle effect and the growth of lithium dendrites, so that the lithium-sulfur battery can still maintain a high capacity after 100 cycles. For example, Figure 6 It can be seen that the lithium-sulfur battery with a coupled nickel-cobalt diatomic catalyst carbon-based material modified diaphragm prepared in Example 1 has a capacity of 1080.8 mAhg -1 The initial capacity is high, and the capacity is maintained at 939.0 mAh g after 100 cycles. -1 , the capacity retention rate is 86.9%.

[0112] (2) Rate performance test

[0113] The rate performance of the lithium-sulfur batteries assembled in Examples 1-3 and Comparative Example 1 was tested on a Xinwei test instrument. The results are as follows: Figure 7 shown.

[0114] Since the lithium-sulfur battery separator is modified by coupling nickel-cobalt diatomic catalyst carbon-based materials, nickel single-atom catalyst carbon-based materials and cobalt diatomic catalyst carbon-based materials, the coupled nickel-cobalt diatomic catalyst carbon-based materials, nickel single-atom catalyst carbon-based materials and cobalt diatomic catalyst carbon-based materials have high catalytic activity and strong anchoring ability for polysulfides, inhibiting the shuttle effect, accelerating the redox reaction, preventing the generation of "dead sulfur", and improving the utilization rate of active sulfur. Figure 7 It can be seen that the capacity of Example 1 at 0.5C, 1.0C, 2.0C and 3.0C is 1089 mAh g –1 , 978mAh g –1 , 891mAhg –1 and 827mAh g –1 After high-rate charge and discharge, when it returns to 0.5C rate, it can still show 1033mAhg –1 The discharge capacity shows that lithium-sulfur batteries have excellent rate performance.

[0115] The above-mentioned embodiments only express the specific implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the protection scope of the present application. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the technical solution concept of the present application, and these all belong to the protection scope of the present application.

Claims

1. A lithium-sulfur battery bifunctional diaphragm, characterized in that: It includes a diaphragm substrate and a load slurry, wherein the load slurry is coated on the surface of the diaphragm substrate; The supported slurry includes an electrocatalyst material, and the electrocatalyst material is a single-atom catalyst carbon-based material / a double-atom catalyst carbon-based material.

2. A lithium-sulfur battery bifunctional diaphragm according to claim 1, characterized in that: The single-atom catalyst carbon-based material is a nickel single-atom catalyst carbon-based material or a cobalt single-atom catalyst carbon-based material; The diatomic catalyst carbon-based material is a nickel-cobalt diatomic catalyst carbon-based material.

3. A lithium-sulfur battery bifunctional diaphragm according to claim 2, characterized in that: The nickel-cobalt diatomic catalyst carbon-based material is prepared by the following method: Step S1: first synthesizing bimetallic Zn / Co-ZIFs by a common solvent method; Step S2: Ni 2+ adsorbed on bimetallic Zn / Co-ZIFs to form Zn / Co / Ni-ZIFs precursor; Step S3: finally pyrolyzing and carbonizing the Zn / Co / Ni-ZIFs precursor; Step S4: acid-wash the product of step S3 to obtain a nickel-cobalt diatomic catalyst carbon-based material.

4. A lithium-sulfur battery bifunctional diaphragm according to claim 3, characterized in that: The nickel-cobalt diatomic catalyst carbon-based material is specifically prepared by the following method: Step S1: Mixing a methanol solution of zinc nitrate and cobalt nitrate with a methanol solution of methylimidazole, stirring, centrifuging, and drying to obtain a product Zn / Co-ZIFs; Step S2: ultrasonically disperse the product obtained in step S1 in cyclohexane, dropwise add nickel nitrate aqueous solution, stir, centrifuge, and dry to obtain precursor Zn / Co / Ni-ZIFs; Step S3: transferring the precursor Zn / Co / Ni-ZIFs obtained in step S2 into a tube furnace and pyrolyzing it under Ar atmosphere; Step S4: soak the pyrolysis product prepared in step S3 in a sulfuric acid solution, wash it by centrifugation with deionized water until the pH reaches neutral, and vacuum dry it to obtain a lithium-sulfur battery diaphragm modification material coupled with a nickel-cobalt diatomic catalyst carbon-based material.

5. A lithium-sulfur battery bifunctional diaphragm according to claim 4, characterized in that: In step S3, the temperature was set at 5.0°C min in an Ar atmosphere. -1 The pyrolysis was carried out at a heating rate of 900°C to 940°C, and the temperatures at 400°C and 800°C were maintained for 1 h respectively, and the final temperature was maintained for 5 h.

6. A lithium-sulfur battery bifunctional diaphragm according to claim 5, characterized in that: The final temperature is 910°C-940°C.

7. A lithium-sulfur battery bifunctional diaphragm according to claim 6, characterized in that: The final temperature was 920°C.

8. A lithium-sulfur battery bifunctional diaphragm according to claim 1, characterized in that: The thickness of the load slurry coated on the surface of the diaphragm substrate is 100 μm-150 μm.

9. A lithium-sulfur battery bifunctional diaphragm according to claim 1, characterized in that: The loading slurry also includes a binder and a conductive carbon material.

10. A nickel-cobalt diatomic catalyst carbon-based material, characterized in that: Prepared by the following method: Step S1: Mixing a methanol solution of zinc nitrate and cobalt nitrate with a methanol solution of methylimidazole, stirring, centrifuging, and drying to obtain a product Zn / Co-ZIFs; Step S2: ultrasonically disperse the product obtained in step S1 in cyclohexane, dropwise add nickel nitrate aqueous solution, stir, centrifuge, and dry to obtain precursor Zn / Co / Ni-ZIFs; Step S3: transferring the precursor Zn / Co / Ni-ZIFs obtained in step S2 into a tube furnace and pyrolyzing it under Ar atmosphere; Step S4: soak the pyrolysis product prepared in step S3 in a sulfuric acid solution, wash it by centrifugation with deionized water until the pH reaches neutral, and vacuum dry it to obtain a lithium-sulfur battery diaphragm modification material coupled with a nickel-cobalt diatomic catalyst carbon-based material.

Citation Information

Cited By

  • Lithium-sulfur battery modified diaphragm as well as preparation method and application thereof

    CN120280654A

  • A co n4 catalyst modified battery separator and its use

    CN122638713A